2018
DOI: 10.1042/bsr20180658
|View full text |Cite
|
Sign up to set email alerts
|

No association between HMGB1 polymorphisms and cancer risk: evidence from a meta-analysis

Abstract: The aim of the present study was to determine whether High mobility group box 1 (HMGB1) polymorphism was associated with cancer susceptibility. PubMed, Embase, and ISI Web of Science were extensively searched without language restriction. Data were extracted using a standardized data collection sheet after two reviewers scanned studies independently. The association between HMGB1 polymorphism and cancer risks was indicated as odds ratio (OR) along with its related 95% confidence interval (95%CI). Meta-analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 49 publications
1
6
1
Order By: Relevance
“…Compared with the former meta-analysis conducted by Kumari T et al 8 , this study have obtained clear conclusions that rs1045411 polymorphism increased cancer risk in some genetic models, especially in the comparison of TT vs. CC+TC while statistical significance was not achieved in any genetic model for all polymorphisms studied by Li XY et al 7 , probably because more studies with larger sample size were included in this meta-analysis and the number of subjects studied was high. Subgroup analysis was also performed by the type of malignancy and ethnicity stratification in the current study, however, no obvious differences were found in the tumour risks in the HMGB1 rs1045411 polymorphism amongst the cancer types except for breast cancer and hepatocellular carcinoma.…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…Compared with the former meta-analysis conducted by Kumari T et al 8 , this study have obtained clear conclusions that rs1045411 polymorphism increased cancer risk in some genetic models, especially in the comparison of TT vs. CC+TC while statistical significance was not achieved in any genetic model for all polymorphisms studied by Li XY et al 7 , probably because more studies with larger sample size were included in this meta-analysis and the number of subjects studied was high. Subgroup analysis was also performed by the type of malignancy and ethnicity stratification in the current study, however, no obvious differences were found in the tumour risks in the HMGB1 rs1045411 polymorphism amongst the cancer types except for breast cancer and hepatocellular carcinoma.…”
Section: Discussioncontrasting
confidence: 50%
“…HMGB1 is a tumour-related gene 28 , and its overexpression of HMGB1 is associated with the hallmarks of cancer 29 , such as unlimited replicative potential, ability to develop blood vessels, evasion of programmed cell death, self-sufficiency in growth signals, insensitivity to inhibitors of growth, inflammation, tissue invasion and metastasis 30 . Because the HMGB1 rs1045411 polymorphism is closely correlated with altered binding of miR-505-5P in the 3'-UTR of mRNA transcripts, HMGB1 gene polymorphisms could emerge as a crucial player in cancer development through a post-transcriptional mechanism 7 , 25 . Furthermore, since the rs1045411 polymorphism resides in the 3'-flanking regions, suggesting a role in mRNA stability as miRNAs can bind the 3'-UTR regions of mRNA transcripts and inhibit HMGB1 expression at the post-transcriptional level 25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have associated HMGB1 SNPs with increased cancer risk, disease susceptibility, severity, and progression, or poorer response to treatment [ 22 , 23 , 27 , 31 , 33 , 42 , 46 , 47 , 48 , 49 ]. However, other studies have indicated that the HMGB1 SNPs are associated with a lower risk of cancer and a less invasive disease [ 26 , 50 ], or may even not be associated with the risk of cancer [ 51 ]. Of note, no information on HMGB1 polymorphisms and prostate cancer risk was mentioned or discussed in the meta-analysis conducted by Li et al [ 51 ], so the correlations of HMGB1 SNPs with prostate cancer risk and disease progression remain uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have indicated that the HMGB1 SNPs are associated with a lower risk of cancer and a less invasive disease [ 26 , 50 ], or may even not be associated with the risk of cancer [ 51 ]. Of note, no information on HMGB1 polymorphisms and prostate cancer risk was mentioned or discussed in the meta-analysis conducted by Li et al [ 51 ], so the correlations of HMGB1 SNPs with prostate cancer risk and disease progression remain uncertain. We found no statistically significant association between the HMGB1 polymorphic variants and prostate cancer patients, implying that the direct impact of HMGB1 SNPs on prostate cancer susceptibility might be limited ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%